2012
DOI: 10.1002/adma.201202361
|View full text |Cite
|
Sign up to set email alerts
|

High Aspect Ratio Sub‐15 nm Silicon Trenches From Block Copolymer Templates

Abstract: High-aspect-ratio sub-15-nm silicon trenches are fabricated directly from plasma etching of a block copolymer mask. A novel method that combines a block copolymer reconstruction process and reactive ion etching is used to make the polymer mask. Silicon trenches are characterized by various methods and used as a master for subsequent imprinting of different materials. Silicon nanoholes are generated from a block copolymer with cylindrical microdomains oriented normal to the surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
82
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 29 publications
1
82
0
Order By: Relevance
“…Reconstruction in a selective solvent is a convenient way of obtaining a porous polymer template of PS-b-PEO BCP. The use of ethanol, a good solvent for PEO but a bad solvent for PS, allows for fabrication of a hexagonally packed porous polymer template of PS-b-PEO [74]. In another study, it was shown that HI acid cleaves the PEO domains in PS-b-PEO, producing porous PS templates [75].…”
Section: (A) Ps-b-pi and Ps-b-pbmentioning
confidence: 99%
See 2 more Smart Citations
“…Reconstruction in a selective solvent is a convenient way of obtaining a porous polymer template of PS-b-PEO BCP. The use of ethanol, a good solvent for PEO but a bad solvent for PS, allows for fabrication of a hexagonally packed porous polymer template of PS-b-PEO [74]. In another study, it was shown that HI acid cleaves the PEO domains in PS-b-PEO, producing porous PS templates [75].…”
Section: (A) Ps-b-pi and Ps-b-pbmentioning
confidence: 99%
“…For example, Gu et al [74] used a solvent-annealed and reconstructed PS-b-PEO mask to pattern high-aspect-ratio silicon holes using SF 6 and O 2 lowtemperature RIE (etch recipe: flow rate 34 sccm SF 6 and 16 sccm O 2 , RF power 1000 W, 10 mTorr pressure and a temperature of −120 • C). The low-temperature etching was used to condense a passivation layer on the sidewall of the silicon, which allows an almost vertical etch profile.…”
Section: (A) Ps-b-pi and Ps-b-pbmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] However, the pattern transfer of the cylindrical phase system is extremely challenging because of the distribution of one block in a matrix of the other and the small diameter of the cylinders which results in poor etch selectivity and shape control. [28][29][30] The pattern transfer performance is generally judged by etch rate, selectivity, uniformity, directionality, etched surface quality and reproducibility. Dielectric materials (SiO2, Al2O3 and Si3N4 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Some periodic nanostructures of Si and SiO2 have been successfully fabricated with this technology in recent years [15][16][17]. Despite the numerous advantages and fruitful achievements of patterning nanostructures offered by the self-assembly, there are some challenges to restrict the patterning transfer of block copolymer patterns to various substrate materials.…”
Section: Introductionmentioning
confidence: 99%